Emergent literacy initatives of the Quezon City public library with implications for the development of a formal program - Mendoza, Camille Laureta L. (2016)
The research focused on the emergent literacy development initiatives of the Quezon City Public Library (QCPL). It aimed to determine observable practices of QCPL Escopa 3 in delivering services that support the emergent literacy skills of children.